Identification and genetic characterization of mitochondrial citrate transporters in Aspergillus niger - Cao, Wei; Zhang, Licheng; Wu, Liu; Zhang, Mingyi; Liu, Jiao; Xie, Zhoujie; Liu, Hao (Frontiers in Microbiology, 2022)
Aspergillus niger is a major cell factory for citric acid production, and the process of citrate export from mitochondria to cytoplasm is predicted to be one of rate-limiting steps in citric acid accumulation. Currently, the mitochondrial citrate transporters (Ctps) in A. niger are not fully characterized. Here, six putative Ctp encoding genes (ctpA to ctpF) were identified based on their homology with a mitochondrial citrate transporter ScCtp1 from Saccharomyces cerevisiae. Disruption of individual ctpA to ctpF caused varying degrees of decline in citric acid accumulation at different fermentation stages, whereas a mutant strain S1696 with disruption of all six ctps showed complete loss of citiric acid production. S1696 also exhibited delayed growth, reduced conidia formation, and decreased pigmentogenesis. Exogenous addition of citrate partially restored the conidia formation and pigmentogenesis in S1696 mutant. Reintroduction of individual ctps (ctpA to ctpF) into S1696 at the amyA locus showed that ctpA, ctpB, and ctpD restored the citric acid titers to 88.5%, 93.8%, and 94.6% of the parent strain, respectively. Additionally, the formation of conidia and pigment production was partially restored after reintroduction of ctpA, ctpB, or ctpD. Overexpression of respective ctpA, ctpB, and ctpD in the parent strain resulted in increases in citric acid accumulation by 32.8%, 19.3%, and 24.2%, respectively. These results demonstrate that CtpA, CtpB, and CtpD play important roles in citric acid transport across the mitochondrial membrane and function in a redundant manner. Enhancement of citric acid transport process can serve as a target for boosting citric acid accumulation in A. niger.